Using Predictive Prefetching to Improve World Wide Web Latency - Padmanabhan, Venkat; Mogul, Jeffrey (ACM SIGCOMM Computer Communication Review, 1996)
The long-term success of the World Wide Web depends on fast response time. People use the Web to access information from remote sites, but do not like to wait long for their results. The latency of retrieving a Web document depends on several factors such as the network bandwidth, propagation time and the speed of the server and client computers. Although several proposals have been made for reducing this latency, it is difficult to push it to the point where it becomes insignificant. This motivates our work, where we investigate a scheme for reducing the latency perceived by users by predicting and prefetching files that are likely to be requested soon, while the user is browsing through the currently displayed page. In our scheme the server, which gets to see requests from several clients, makes predictions while individual clients initiate prefetching. We evaluate our scheme based on trace-driven simulations of prefetching over both high-bandwidth and low-bandwidth links. Our results indicate that prefetching is quite beneficial in both cases, resulting in a significant reduction in the average access time at the cost of an increase in network traffic by a similar fraction. We expect prefetching to be particularly profitable over non-shared (dialup) links and high-bandwidth, high-latency (satellite) links.